Stenting of the right ventricular outflow tract as an initial intervention in Tetralogy of Fallot with pulmonary stenosis and major aortopulmonary collateral arteries. (4th March 2021) - Abumehdi, Mohammad; Sasikumar, Deepa; Chaudhari, Milind; Bhole, Vinay; Botha, Phil; Mehta, Chetan; Stumper, Oliver
Abstract: Objectives: To assess the role of right ventricular outflow tract stenting as the primary intervention in Tetralogy of Fallot with pulmonary stenosis and major aortopulmonary collateral arteries. Background: The management of a subset of infants with Tetralogy of Fallot with pulmonary stenosis and major aortopulmonary collateral arteries requires a staged approach including rehabilitation of diminutive native pulmonary arteries, conventionally using an aortopulmonary shunt. We share our experience of pulmonary artery rehabilitation with right ventricular outflow tract stenting. Methods: Retrospective review of all patients with Tetralogy of Fallot with pulmonary stenosis who underwent right ventricular outflow tract stenting as primary intervention over an 8-year period. Results: Ten patients underwent right ventricular outflow tract stent insertion at a median age of 61 days (interquartile range (IQR) 8.3–155 days). Median weight at stent deployment was 4.2 kg (IQR 3.2–5.7 kg). Oxygen saturations improved from a median of 79% (IQR 76–80%) to 92% (IQR 90–95%), p = 0.012. The median right and left pulmonary artery z score increased from −3.51 (IQR −4.59 to −2.80) and −2.07 (IQR −3.72 to 0.15) to a median of −1.17 (IQR −2.26 to 0.16) p < 0.05, and 0.24 (IQR −1.09 to 1.84) p < 0.05, respectively, at subsequent angiogram. Nine patients underwent further catheterisation. Four patients underwent complete anatomical repair. Only one patient required unifocalisation, as most patients had a native supply to all-important lung segments. Conclusion: Right ventricular outflow tract stenting is a useful procedure in the subset of patients with Tetralogy of Fallot with pulmonary stenosis and major aortopulmonary collateral arteries, where native pulmonary arterial growth is required to facilitate repair.